Dissolution of Non-cohabiting Relationships and Changes in Life Satisfaction and Mental Health - Preetz, Richard (Frontiers in Psychology, 2022)
This study investigates how individuals’ life satisfaction and depression are affected by the dissolution of a steady non-cohabiting intimate relationship. Previous studies have focused more on the consequences of divorce and less on the influence of non-cohabiting relationships on the well-being of the individual. The data for this study were taken from pairfam, a large-scale German panel survey, and were used to estimate fixed-effects panel regression models and impact functions to identify the overall effect of dissolution and trajectories after separation. The study sample comprised 2,631 individuals who were observed over the course of 11,219 partnership years. Based on the results of this study, three main findings were reported. First, the dissolution of a non-cohabiting relationship led to a significant decline in mental health and life satisfaction. Second, the trajectories after dissolution suggest that the decline was only temporary, showing readjustment after 1 year. Third, gender differences were identified, suggesting worse consequences for men who experienced a significant decline in both dimensions and did not readjust in life satisfaction until several years after the dissolution. For women, decreases were only found for life satisfaction, but quick readjustments were observed.